Retroperitoneal Mature Cystic Teratoma in a Neonate: A Case Report - Patil, Prashant Sadashiv; Kothari, Paras; Gupta, Abhaya; Dikshit, Vishesh; Kamble, Ravi; Kekre, Geeta; Deshmukh, Shahaji (Journal of Neonatal Surgery, 2016)
We report a case of retroperitoneal mature cystic teratoma in a 2-day-old neonate. Diagnostic and surgical procedure including its complexity and relevant literature review has been discussed.